A Rapid and Efficient Method for In Vitro Screening of Taro for Leaf Blight Disease Caused by Phytophthora colocasiae. Issue 7 (4th March 2016) - Nath, Vishnu Sukumari; Basheer, Shyni; Jeeva, Muthulekshmi Lajapathy; Hegde, Vinayaka Mahabaleswar; Devi, Asha; Misra, Raj Shekar; Veena, Syamala Swayamvaran; Raj, Mithun
Abstract: Taro leaf blight caused by Phytophthora colocasiae presents the single biggest constraint for taro cultivation globally. To accelerate breeding and selection for disease resistance to leaf blight, it is important to develop bioassays which could differentiate resistant and susceptible cultivars efficiently. In this study, thirty taro accessions and four released cultivars were evaluated for resistance to leaf blight using a modified floating leaf disc assay. A novel method for mass production of P. colocasiae zoospores was developed and used as inoculum for the assay. There were significant (P   <   0.05) differences among accessions in their response to P .  colocasiae infection in the detached leaf assay. The accessions could be efficiently classified into various resistance groups based on a 0–4 score. Also, the assay results were consistent with the field evaluation scores of taro accessions. Thus, this study reports the development of a rapid, simple and repeatable assay that can be used to screen large numbers of taro cultivars for resistance to P. colocasiae .